Multimodality in the Textbook œEnglish in Mind 3 For Tenth Grade Students of SMAN 7 Binjai - Salda, Mutiara Putri; Hartoyo, Indra (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This study aimed to investigate multimodality component, verbal and visual modes in textbookœEnglish in Mind 3. This study was conducted by using descriptive qualitative researchmethod by Miles, Huberman and Saldana (2014). The data used from 4 welcome sections and14 chapters in the textbook œEnglish in Mind 3 for Tenth Grade Students. The data werecollected through observation checklist. The data collected relates to the components ofmultimodality, verbal modes and visual modes, in the reading section of each welcome sectionand chapter. This study applied the theory of multimodal, for verbal modes is SystemicFunctional Linguistic by Halliday (1994) and for visual modes is Reading Images by Kressand van Leeuwen (2006). The results of this study are verbal and visual modes have beenrepresented in each chapter of the textbook. Overall, the compatibility between verbal modesand visual modes in supporting the conveying of meaning has also been described well,although there are still some discrepancies. It was also found that this textbook is suitable foruse in learning English related to multimodality.